Sedentary Behavior, Physical Activity and Body Composition in Adults - De Moraes-Ferrari, G (Associacao Medica Brasileira, 2020)
OBJECTIVE: We investigated the associations between objectively assessed sedentary behavior (SB) and moderate-to-vigorous physical activity (MVPA) and body composition variables among a representative sample of Brazilian adults. METHODS: Using an accelerometer, SB and MVPA were monitored for at least 5 days in 524 participants (261 men; age, 18-65 years). Each minute epoch was classified as sedentary or spent in light, moderate, or vigorous physical activity (LPA, MPA, and VPA, respectively). The measured body composition variables included abdominal perimeter (AP) and neck circumference (NC). RESULTS: Men accumulated significantly more min/day of MPA (37.82 versus 27.28), VPA (1.10 versus 0.31), MVPA (39.02 versus 27.61), and steps/day (14,978 versus 13,443) than women (p<.001). In men, MPA, VPA, MVPA, and steps/day were negatively associated with AP (p<.05) independently of SB. Only VPA was significantly associated with NC (β= 0.113; p=.002). In women, only SB was significantly associated with AP (β= 0.003; p=.031). There were no significant associations between physical activity intensities and body composition in women. CONCLUSIONS: Our findings on the unequal association of physical activity with body composition variables between sexes can help inform future intervention strategies in Brasil. © 2020 Associacao Medica Brasileira. All rights reserved.